INTERPLAY BETWEEN INTESTINAL MICROBIOTA AND RISK FACTORS IN THE FIRST THREE YEARS OF LIFE - Alexandru Cosmin Pantazi; Mustafa Ali Kassim Kassim; Wassan Nori; Cristina Maria Mihai; Tatiana Chisnoiu; Adriana Luminița Bălașa; Larisia Mihai; Corina Elena Frecuș; Adina Ungureanu; Viviana Cuzic; Anca Daniela Pînzaru; Simona Claudia Cambrea (Romanian Society of Oral Rehabilitation, 2023)
Introduction. Gut microbiota is a microecosystem with a dynamic complexity, influenced by multiple factors, with impact on the composition and long-term health. An imbalance in gut microbiota, often termed as 'dysbiosis', is associated with a wide variety of pediatric diseases, including allergies, diabetes mellitus, autoimmune diseases, autism spectrum disorders and celiac disease. The aim of the study is to emphasize the main clinical manifestations and to analyze the risk factors of gut dysbiosis in the first three years of life. Material and Methods. The retrospective study was conducted on a period between 2020-2022, including children aged between 0-3 years with intestinal dysbiosis, aiming to analyses the factors predisposing to imbalance in gut composition according to age, gender, environmental factors, personal medical history, clinical manifestations, and laboratory data. Results and Discussions. Main clinical manifestations of dysbiosis in the first three years of life are represented by abdominal pain, vomiting, irritability, diarrheal stools and stools with mucus. C-section represents a major risk factor for the occurrence of gut dysbiosis in infants. Low birth weight is a risk factor due to imbalance of intestine function and high susceptibility to dysbiosis. Infant formulas determine a low concentration of beneficial bacteria. Urban area represents an environmental factor with increased susceptibility of subjects for gut dysbiosis. Antibiotherapy in the first year of life is a factor which determines a low microbial diversity in infants. Conclusions. The interplay between intestinal microbiota, environment and host is a multidirectional relationship. Factors such as mode of delivery, type of feeding, weight, living conditions and antibiotherapy have an influence on the modulation of the microbiological milieu in the first three years of life, with impact on long-term health.